N-Functionalization of 1,2-Azaborines - Lee, Hyelee; Alvarado, Marisol; Ingram, Sarah; Li, Bo; Liu, Shih-Yuan (Synlett, 2023)
General protocols for the N-functionalization of 1,2-azaborines with C(sp3), C(sp2), or C(sp) electrophiles are described. The syntheses of a new parental BN isostere of trans-stilbene and a BN isostere of a lisdexamfetamine derivative were accomplished with the developed methodology.
Keywords: azaborines; cross-coupling; BN heterocycles; N-functionalization; amination